PEDAGOGICAL CONDITIONS FOR FORMATION HEALTHY LIFESTYLE CULTURES FOR STUDENTS (Pedagogy of Higher and Secondary Education, 2008)
The article deals with some problems concerning the formation of the students culture of healthy way of lift; some definitions of the theme researched; pedagogical conditions of the formation of students culture of healthy way of life.